Anti-diabetic Agents and the Potentials for Reducing Cardiovascular Risks in Type-2 Diabetes Mellitus - Ezeani IU; Eregie A; Ohwovoriole AE (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Recent reports from Cardiovascular Outcome Trials (CVOTs) revealed that some newer anti-diabetic drugs impact Major Adverse Cardiovascular Events (MACE). These medications include the Sodium-Glucose Co-Transporter (SGLT2) inhibitors and the Glucagon-like Peptide-1 (GLP-1) receptor agonists. There is a need for a review of the mechanisms of action of these drugs, in addition to their glucose-lowering effects and CV benefits. This review paper aims to explore the cardio-protective effects and CV risks of anti-diabetic medications, their mechanisms of action and the CV benefits evidenced by CVOTs. Using internet search, with search items such as Type 2 Diabetes mellitus, cardiovascular risk factors, cardiovascular outcome trials, major adverse cardiovascular events, sodium-glucose transporter-2 inhibitors, glucagon-like peptide-1 receptor agonist, the Google Scholar, EMBASE, PubMed, Medline, Web MD, and Scopus were checked for various relevant published articles. Analyses of the results of multiple CVOTs from various parts of the world were considered. These CVOTs were reviewed to assess the role of anti-diabetic agents in reducing cardiovascular risk in patients with T2DM. The SGLT2 inhibitors and GLP1 agonists were found to be beneficial in lowering MACE when compared with placebo. This is in addition to their anti-hyperglycaemic benefits. In conclusion, SGLT2 inhibitors and GLP-1 agonists confer dramatic beneficial CV risk reduction on patients with T2DM, as shown by the various CVOTs. This is in addition to their anti-hyperglycaemic effects. This remarkable benefit justifies the need by various guidelines to adopt them as second line agents to metformin in managing patients with T2DM.